The Feynman Propagator to Model Molecular Communications Between an Engineered Nanodevice and Beta Cells - Nieto-Chaupis, Huber (2020)
In a prospective scenario of nanomedicine, an engineered cargo of nanoparticles would be crucial to alleviate diseases that might to require of a precise doses of biochemical compounds in situ. In this paper, the technique of Feynman's propagator to estimate the probability amplitude in the different paths of a charged nanoparticle that would opt to reach a beta cell, is employed. The aim is to generate the artificial releasing of granules of insulin in beta cells to avoid hyperglycemia in those diabetes patients. For this end the quantum mechanics evolution operator is employed. Once the square of the amplitudes are calculated, it leads to analyzed the cases in where repulsive electric forces might to cause to decrease the chance of nanoparticle to go through the cell. Computational simulations are presented.